2004
DOI: 10.1080/08035250310007952
|View full text |Cite
|
Sign up to set email alerts
|

One-third of term babies after perinatal hypoxia-ischaemia have transient hearing impairment: dynamic change in hearing threshold during the neonatal period

Abstract: Hearing threshold is elevated in about one-third of term babies after hypoxia-ischaemia. The elevated threshold decreases progressively after birth, and returns to normal by one month in most babies. The threshold correlates weakly with the severity of encephalopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This infection can cause localized placental hypoxia through direct damage to the placental villi [32] . And yet, perinatal hypoxia is one cause of transitory or permanent HL in newborns [33] . Third, SARS-CoV-2 affects newborns after being transmitted vertically through the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…This infection can cause localized placental hypoxia through direct damage to the placental villi [32] . And yet, perinatal hypoxia is one cause of transitory or permanent HL in newborns [33] . Third, SARS-CoV-2 affects newborns after being transmitted vertically through the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal hypoxic ischemic encephalopathy, a common disease in perinatal neonates, can cause various neurological sequelae, including epilepsy, cerebral palsy, visual impairment, and mental retardation. Sensorineural hearing loss is a severe complication that is associated with perinatal hypoxia and ischemia [ 1 , 2 ]. Jiang et al reported that 16.2% of infants with perinatal hypoxia-ischemia also presented with impaired cochlear hair cell function [ 3 ].…”
Section: Introductionmentioning
confidence: 99%